Desafios e possibilidades do estágio remoto em Psicologia Escolar em tempos de Covid-19 - Cardoso, Rita de Cássia da Silva (Brasil, 2022)
The school is an essential role in the lives of children and adolescents, far beyond the transmission of academic knowledge, such as helping them to build socio-emotional skills. Given this, there are many possible contributions to Psychology, the main factor being to help educators in the construction of a transformative educational practice. In 2020, the whole world needed to strengthen ties between education and technologies, due to the COVID-19 pandemic, especially with regard to the development of virtual classes. In this way, a Supervised Internship was carried out by the Faculty of Psychology of the Federal University of Amazonas with high school students from the Federal Institute of Amazonas - IFAM, with the objective of promoting health and well-being, within the possibilities in the midst of a pandemic scenario. . The present work aims to report this internship experience from the point of view of one of the students of the Psychology course at UFAM.